Analysis and performance evaluation of new coding options for space telecommand links ‐ Part I: AWGN channels. (9th September 2014) - Baldi, M.; Chiaraluce, F.; Garello, R.; Maturo, N.; Aguilar Sanchez, I.; Cioni, S.
Summary We investigate and compare, over the additive white Gaussian noise channel, different options for updating the error correcting code currently used in space mission telecommand links. Besides some more consolidated proposals, using low‐density parity‐check codes, we characterize and assess the performance of alternative schemes, based on parallel turbo codes and soft‐decision decoded Bose‐Chaudhuri‐Hocquenghem (BCH) codes. The analysis considers relevant metrics like the codeword error rate, the frame error rate, and the undetected frame error rate. The considered codes include binary and non‐binary low‐density parity‐check codes, parallel turbo codes and extended BCH codes, with different decoding algorithms. The complexity of the various schemes and possible limits for their application are considered and discussed. Several numerical examples are provided. International Journal of Satellite Communications and Networking. Copyright © 2014 John Wiley & Sons, Ltd.